Comparative study of infiltration rate measurement using double ring infiltrometer and rainfall simulator - RASMI S. N; Yesudas Zacharia; Er. Shyla Joseph (Guide) (Tavanur 2002 Kelappaji College of Agricultural Engineering and Technology)
Comparative study of infiltration rate measurement using double ring infiltrometer and rainfall simulator
Comparative study of infiltration rate measurement using double ring infiltrometer and rainfall simulator